The Unique Ethnocultural Characteristics of the Word ‘Argal’ - WUYUNQIQIGE; Dashdamba, Erdenesan (Mongolian Language and Literature Studies, 2025)
In this article, I have attempted to collect and explain expressions with unique meanings that are connected to the culture of argal—dried dung used as fuel—that developed over centuries within the nomadic traditions of the Mongols. Examining the everyday life, customs, and practices of a nation through the relationship between language and culture is theoretically and practically important for clarifying the close ties between the Mongolian language and culture. Among both Khalkha Mongols and Inner Mongols, there are many curious and distinctive expressions related to the history and culture of argal. They are considered distinctive because these expressions do not simply refer to the general meaning of argal or fuel preparation, but reflect the particular ways people of different regions and communities speak about them. As the living conditions of the Mongols have transformed over time, the meanings of these unique words show how many kinds of changes have taken place around the culture of argal, which served as the main means of fuel preparation. “Аргал”-ын тухайт үг хэллэгийн угсаатны соёлын өвөрмөц шинж Хураангуй: Энэхүү өгүүлэлд монголчуудын нүүдлийн соёлын олон зуун жилийн явцад тогтож бий болсон “Аргал”-ын соёлтой холбоотой өвөрмөц утгатай үг хэллэгийг цуглуулж тайлбарлахыг хичээлээ. Үндэстний ахуй, ёс заншлын баримт хэрэглэгдэхүүнийг хэл - соёл судлалын холбоо харьцаанд судлах нь монгол хэл, соёлын холбоо хамаарлыг тодруулахад онол хэрэглээний ач холбогдолтой юм. Халх, өвөр монголчуудын аргал түүх соёлтой холбоотой сонин содон үг хэллэг олон байна. Сонин содон гэсний учир нь эдгээр үг хэллэг нь аргал түүх, түлшээ бэлтгэх гэх мэт нийтлэг утгатай бус тухайн бүс нутаг, орон нутгийн ард түмэн ярьж хэлэлцдэгээрээ онцлог юм. Монголчуудын ахуй амьдрал цаг үеэ дагаад хувьсан өөрчлөгдөхийн хэрээр түлш бэлтгэх гол тэдний түлээ түлшээ бэлтгэх гол гол хэрэглэгдэхүүн болсон аргалын соёлыг тойрон хэчнээн олон төрлийн өөрчлөлт гарч ирснийг дээрх өвөрмөц үгсийн утгаас харж болно. Түлхүүр үгс: Аргал – монголчуудын нүүдлийн соёл, аргалын түүх соёл, өвөрмөц утгатай үг хэллэг